Die südhemisphärischen Coniferen als genetisches, geographisches und ökologisches Florenelement - Bader, Frido (ERDKUNDE, 1960)
The paper investigates the areas of the southern hemisphere conifer species which, since the Tertiary, have almost exclusively suffered a shrinkage. In contrast to their relations in the northern hemisphere, these southern hemisphere species have not succeeded in adapting themselves to climates with cold winters. A pronounced area, where they are preserved, is found in the islands between New Zealand and New Guinea, which in the Tertiary were linked with the New World via Antarctica. Genetically the southern-hemisphere conifers can thus be called a Pacific-Antarctic element. The present areas of occurrence may be traced back to a circum-Antarctic pantropic-montane area which, however, is fully occupied only by Podocarpus; the other species occur merely in parts of this major area. Ecologically most species can be classified as temperateoceanic and their favourite stannds are in cloud and laurel forests.